Effect of KnowledgeMomentum Organizational Learning Styles Applied Study of View A Sample of KUFA Cement Plant Employees - Researcher / PhD. Hamza Kata Mahdi Al-Shaibani, Prof. Dr.Lamia Salman Al-ZUBAiDI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify the nature of the effect of knowledge momentum levels in determining the methods of organizational learning in the Kufa cement plant, and by relying on the stratified sample method, (135) questionnaires were distributed to a sample of Kufa cement plant employees, and the number of retrieved questionnaires was (125). 120) A valid questionnaire for statistical analysis, with a response rate of (95%), and analyzed with the help of statistical programs (SMEs) and (SPSS v.24). The results showed that there is a direct relationship of influence between levels of knowledge momentum on organizational learning, and highlight the importance of the current research, due to the existence of a knowledge gap represented in the extent to which the effective methods of organizational learning can be selected. The possibility of facing the problems facing workers in the researched organization, increasing their experience, and developing their skills in the workplace.